Does Stock Price Crash of Firms in the Same Business Group Cause Stock Price Crash in Other Member Firm? Evidence from Korea. Issue 7 (28th May 2019) - Kwon, Sewon; Jung, Taejin; Sunwoo, Hee-Yeon; Yim, Sang-Giun
ABSTRACT: This article examines the spillover of stock price crash within business groups. Using Korean business group data, we find that the crash risk of a firm is positively associated with the crash risk of other member firms in the same business group. We also find that crashes spread but do not arise simultaneously across firms within a business group. Further analyses reveal that the documented association is stronger in firms with more inter-company transactions and those with lower market-to-book ratios. Our article contributes to the literature by suggesting that the consequence of opportunistic behaviors of controlling shareholders (i.e., stock crash of a member firm) spills over within business groups.